Effects of an unprecedented summer heatwave on the growth performance, flesh colour and plasma biochemistry of marine cage-farmed Atlantic salmon (Salmo salar). (February 2019) - Wade, Nicholas M.; Clark, Timothy D.; Maynard, Ben T.; Atherton, Stuart; Wilkinson, Ryan J.; Smullen, Richard P.; Taylor, Richard S.
Abstract: Global seawater temperatures are increasing and becoming more variable, with consequences for all marine animals including those in food production systems. In several countries around the world, arming of Atlantic salmon ( Salmo salar ) occurs towards the upper end of the thermal tolerance window for this species, and marked effects on salmon production during summers have been experienced but never empirically investigated. This project tracked the effects of an extreme summer heatwave on two different cohorts of fish stocked into farm cages either during early winter (EW) or late winter (LW). The farm site experienced an unprecedented high water temperature event, with a peak water temperature of 22.9 °C and 117 days above 18 °C. Fish in both EW and LW cohorts experienced a temperature-induced cessation of voluntary feed intake as well as inefficient osmoregulatory, liver and renal function during high temperature periods. Flesh colour declined primarily in the dorsal and ventral regions of the fillet and secondarily along the midline, with over 20% of fish demonstrated a complete loss of flesh colour during the months of March and April. A return to feeding in autumn occurred faster in some fish and caused a marked bimodal size distribution to appear within both the EW and LW cohorts as autumn progressed. However, the LW cohort returned to feeding at seawater temperatures of 20.2 °C, compared with 18.6 °C for the EW cohort. There was a strong positive relationship between fillet colour recovery and residual condition index (RCI). These findings identified alkaline phosphatase as a potential marker to non-destructively track individual fish for signs of recovery after a thermal stress event, and shed light on the physiological consequences of marine heatwaves on fishes. This study also identified that supporting feed intake or promoting a return to feeding may help mitigate the negative impacts of climate warming on cultured Atlantic salmon. Highlights: The farm recorded a peak water temperature of 22.9 °C (5 m) and 117 days > 18 °C. Temperature caused a cessation of voluntary feeding for approximately 2 months. Flesh colour declined during March and April, with complete loss in over 20% of fish. High temperature compromised fish osmoregulatory, liver and renal functions. RCI and plasma AP levels may be useful as a non-destructive indicator of recovery.